Using virtual enviroments to study interactions in sport performance - Correia, V.; Araujo, D.; Watson, G.; Craig, C. (Complex systems in Sport, 2014)
The potential for studying behaviour in sport through virtual environment technology has been outlined. One of the main advantages it offers is to experimentally control the information available and examine how this information guides action in sport. Although such technologies are not yet widely accessible, large displays and body-based interactive devices are becoming increasingly advanced and accessible (e.g. Kinect4, Nintendo Wii). and immersive and interactive sport situations will be easier to simulate while maintaining their functional fidelity.